2022
DOI: 10.1111/nicc.12754
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of prolonged infusion antibiotics during Y‐site administration

Abstract: Background: Antimicrobial resistance is a threat to global public health. The use of prolonged infusions in the hospital setting for certain antimicrobials is widely increasing in order to improve their efficacy and safety, including resistance development.Due to limited vascular access, it is important to clarify whether they can be infused through the same line with other drugs during Y-site administration.Aim: The aim of this review is to update and summarize the evidence on Y-site compatibility of antibact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…One review article was identified through this search; however, it only offered a simplified compatibility chart for 10 antibiotics and 131 commonly used medications. 9 None of the articles included in this assessment are meta-analyses. An additional search was performed utilizing multiple tertiary databases to determine available compatibility information.…”
Section: Methodsmentioning
confidence: 99%
“…One review article was identified through this search; however, it only offered a simplified compatibility chart for 10 antibiotics and 131 commonly used medications. 9 None of the articles included in this assessment are meta-analyses. An additional search was performed utilizing multiple tertiary databases to determine available compatibility information.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, in 2022, Nunez‐Nunez et al reviewed the Y‐site compatibility between antibiotics in prolonged infusion with drugs commonly administered in ICUs. They analysed a total of 1302 drug‐to‐drug potential combinations and presented them in simple 2‐dimensional consultation chart 9 . Despite the extensive summary of evidence carried out, there are some recommendations related to drugs and PN Y‐site compatibility that could pose a risk to patients and should be considered with caution.…”
Section: Drug Concentrationa Vehicle 3‐in‐1 2‐in‐1 Comments Referencesmentioning
confidence: 99%
“…Finally, we consider it advisable to divide the compatibility recommendations based on the PN admixture types (3‐in‐1 or 2‐in‐1). After reviewing this paper 9 and the other references, we propose the following guide (Table 1) in administering selected antibiotics with PN.…”
Section: Drug Concentrationa Vehicle 3‐in‐1 2‐in‐1 Comments Referencesmentioning
confidence: 99%
See 1 more Smart Citation
“…This issue features six reviews that showcase some different review types: two systematic reviews with a meta‐analysis 4,5 ; two systematic reviews without a meta‐analysis 6,7 and two scoping reviews 8,9 . These investigate the prevalence of depressive symptoms among intensive care nurses and the effect of enteral immunomodulatory nutrition formula on the outcomes of critically ill patients; targeted temperature management in acute liver failure and the compatibility of prolonged antibiotic infusion administration; and the use of virtual reality in intensive care units and educational interventions to reduce the use of physical restraints, respectively.…”
mentioning
confidence: 99%